IMPLEMENTASI ENTREPRENEUR SYARIAH PADA TOKO SANTRI SYARIAH SURAKARTA - Muhammad Syamsuri; Mahfud Maulana Zulfa Ramadhan; Khoirul Fikri (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This research was conducted with the aim of knowing and understanding the practices of sharia entrepreneurs conducted by the Santri Syariah Shop having its address at Jalan Yos Sudarso No. 21, Kauman, Pasar Kliwon, Surakarta. Site selection was made because this business venture is one of the many businesses that are quite successful in the Surakarta region, and because it carries the name of sharia in its business so it needs to be further investigated regarding the application of Islamic values and its compatibility with the principles of sharia entrepreneurs. The research method used is a qualitative research method with data analysis techniques used is phenomenological analysis. Data obtained directly through observation to the research site and conducting interviews with related parties such as managers, other employees, and also consumers who then analyzed the results. The results show that the Santri Syariah Shop runs its business activities based on Islamic values both in terms of managing and running its business. The principles of sharia entrepreneurs in managing their business are applying employee recruitment that requires observance of worship, giving compensation before maturity, avoiding usury from cooperation with conventional banks, and guaranteeing halal products from the production process to marketing. And in carrying out its business, applying business character that is honest, fair, communicative or capable, safeguarding the rights of consumers, as well as paying zakat, infaq and shodaqoh.Keywords:Â Sharia Entrepreneur Implementation; Business; Entrepreneurship